Synthesis of Polypyrrole Nanocomposites Using Sodium Dodecylbenzenesulfonate and Poly(vinyl alcohol) - Mokhtarifar1, Mojtaba; Sadegh Nabizadeh1, Mohammad; Eisazadeh2, Hossein (Asian Journal of Chemistry, 2011)
In this study, polypyrrole nanocomposites were prepared in the aqueous and aqueous on-aqueous media by using ferric chloride as an oxidant in presence of various surfactants such as sodium dodecylbenzenesulfonate and poly(vinyl alcohol). Morphology, particle size, yield and chemical structure of the product were characterized by using scanning electron micrograph and fourier transform infrared. The results indicate that the morphology, yield and particle size of products are dependent on the type of surfactant. The results also show that the intensity of peaks is dependent on the type of surfactant.